Pembuatan Apotek Hidup atau Tanaman Obat Keluarga (TOGA) di Desa Karanghaur - Sakum; Sarwo Edy; MH Ainulyaqien; Kisanda Midisen; Sukron Mamun (DPPM Universitas Pelita Bangsa, 2021)
In post-pandemic conditions like now, the cultivation of live medicinal plants is very important. This can be an alternative to traditional medicine to overcome various complaints and diseases. In addition, during this period, each individual needs a strong immune system. One form of realising the utilisation of existing land in the village or region is to plant a live pharmacy, in order to enable daily needs. This community service activity is carried out through three stages of implementation methods. The first stage was the lecture/presentation method. The second stage also uses the material discussed in the second stage is about how to cultivate medicinal plants. The third stage is a demonstration of making a living pharmacy through the cultivation of family medicinal plants (TOGA). The planting of live pharmacy plants began with clearing the empty land, pulling out grass and sweeping up rubbish. The soil was also loosened with a hoe to remove weeds and dirt. Seedlings of plants such as turmeric, ginger, kencur, lemongrass, and galangal are processed before planting. The rhizomes of seeds such as turmeric, ginger, galangal, and kencur are dried in the sun and placed in a moist place to grow tuna. Meanwhile, lemongrass seeds are taken from mature plants and cut off the ends. After hiding, the plants need to be cared for with regular watering so that they develop well. The cultivation of live pharmacy plants has a positive economic impact, increasing the number of entrepreneurs, especially in the field of herbal medicine. this activity aims to increase public awareness and knowledge about the benefits of medicinal plants and make a positive contribution in the economic and health fields. The point is to be able to develop other variations of medicinal plants by propagating them on less functional land, and to be able to cultivate their survival for residents properly.